2012
DOI: 10.1038/oby.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Deficiency Is Associated With Increased Adiposity and Insulin Resistance

Abstract: Adropin is a secreted peptide that improves hepatic steatosis and glucose homeostasis when administered to diet-induced obese mice. It is not clear if adropin is a peptide hormone regulated by signals of metabolic state. Moreover, the significance of a decline in adropin expression with obesity with respect to metabolic disease is also not clear. We investigated the regulation of serum adropin by metabolic status and diet. Serum adropin levels were high in chow-fed conditions and were suppressed by fasting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
208
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(219 citation statements)
references
References 28 publications
9
208
2
Order By: Relevance
“…Whole-body AdrKO and AdrTG on a C57BL/6J (B6) background were described previously (1,2). Wild-type (WT) B6 mice were purchased from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-body AdrKO and AdrTG on a C57BL/6J (B6) background were described previously (1,2). Wild-type (WT) B6 mice were purchased from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Transgenic over expression or systemic adropin treatments markedly attenuate insulin resistance and glucose intolerance in diet-induced obese mice (Kumar et al 2008). In line with these observations, adropin knockout mice were associated with increased hepatosteatosis, adiposity and insulin resistance (Ganesh Kumar et al 2012). Even though the linkage between circulating adropin levels and other various pathophysiological conditions in mammals have been reported, the exact link with adropin remains elusive.…”
Section: Introductionmentioning
confidence: 91%
“…Besides, adropin may be involved in the metabolic adaptation to fasting, although these data are still controversial. In fasting mice, adropin expression is attenuated compared with control values (Kumar et al 2008), whereas plasma adropin levels in humans do not change in response to fasting (Ganesh Kumar et al 2012). Unlike its mammalian counterparts, the physiological significance of adropin is still poorly understood in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Adropin is a peptide hormone, encoded by the energy homeostasis-associated gene ( Enho ) that is involved in the regulation of metabolic homeostasis in mice [45,46]. Aydin et al [47] found that women with GDM had lower adropin concentrations in their colostrum than women without GDM, but that adropin levels were not different in transitional (7 days postpartum) and mature milk between groups.…”
Section: Gestational Diabetes Mellitus and Breast Milk Compositionmentioning
confidence: 99%
“…Aydin et al [47] found that women with GDM had lower adropin concentrations in their colostrum than women without GDM, but that adropin levels were not different in transitional (7 days postpartum) and mature milk between groups. It has been demonstrated that adropin deficiency is associated with higher body fat mass in mice, suggesting that being exposed to lower levels of adropin from GDMBM may also lead to an increased body fat mass in children , as in mice [46]. Furthermore, irisin is a myokine involved in thermogenesis by inducing conversion of white adipose tissue into brown adipose tissue [48].…”
Section: Gestational Diabetes Mellitus and Breast Milk Compositionmentioning
confidence: 99%